Implikasi Perjanjian Kemitraan Ekonomi Komprehensif Indonesia-Australia (IA-CEPA) terhadap Perdagangan Luar Negeri Indonesia - Yeti Andriani (Andalas Journal of International Studies (AJIS), 2017)
This research is used to see IA-CEPA's contribution to trade of both countries especially to Indonesian foreign trade. With the research question, what is the economic implication of this economic partnership agreement politics, especially related to Indonesian trade sector? Adam Smith's theory in this research is that the liberal economy is closely related to the world economic development, an idea that requires the liberty of individuals or economic units to achieve their interests and an invisible hand can facilitate economic regulation and achieve high economic efficiency and growth, the government should not interfere and instead let the market run on its own mechanism. Added by David Ricardo that mutual interest is generated is a mutual interest-based benefit of the trade. The method used is qualitative method that is method with purpose to explain topic in detail. The result of this research is the IA-CEPA agreement can facilitate the access of Indonesian market and foreign trade to Australia.Key Words: Liberal Economics, IA-CEPA, Trade